Evaluation of diagnostic indices of lectin antigen and anti-lectin antibodies in amebic liver abscess - Salam, Md. Abdus (2012)
Objective: Diagnostic indices of Gal/Gal NAc lectin antigen and anti-lectin antibodies for amebic liver abscess were evaluated to see their usefulness. Methodology: Forty (40) clinically suspected cases of liver abscess patients admitted in the Rajshahi Medical College Hospital (RMCH), Bangladesh during January to December 2007 were included. Liver abscess pus from all cases were tested for small subunit of ribosomal RNA (rRNA) gene of Entamoeba histolytica by Real Time PCR and only PCR-positive cases were further analyzed for detection of Gal/Gal NAc lectin antigen and anti-lectin antibodies in their liver abscess aspirates, plasma, saliva and urine using Enzyme-linked immunosorbent assay (ELISA) methods. Except liver abscess pus, all other samples were also tested for 20 patients suffering from diseases other than liver abscess, who served as controls for the study. Results: Out of 40 patients, 39 were PCR-positive and considered as confirmed cases of amebic liver abscess. The rate of detection of lectin antigen and anti-lectin antibody in liver abscess pus was 12.82% and 56.41% respectively. Diagnostic sensitivities of lectin antigen in plasma, saliva and urine were 15.38% (95%CI 6-31%), 07.69% (95%CI 2-22%) and 00% respectively, while sensitivities of anti-lectin antibodies in all those samples were 100% (95%CI 88-100%), 87.17% (95%CI 72-95%) and 56.41% (95%CI 40-78%) respectively. Diagnostic specificities of lectin antigen was 100% in all specimens but for anti-lectin antibodies, specificities were 100% (95%CI 88- 00%) in plasma, 50% (95%CI 28-78%) in saliva and 70% (95%CI 46-87%) in urine. Overwhelming majority of cases (94.87%) received Metronidazole therapy for variable period before sample collection, which is correlated with low rate of antigen detection. Conclusion: Detection of lectin antigen for amebic liver abscess has very limited or no role where Metronidazole is used indiscriminately but detection of anti-lectin antibodies especially in plasma (100% sensitivity) and saliva (87.17% sensitivity) are excellent to satisfactory. Estimation of plasma IgG can be recommended as serodiagnostic tool for symptomatic amebic liver abscess.